The organization of environmental protection administration in Poland and the European Union - Jabłoński, Maciej (Studia Ecologiae et Bioethicae, 2014)
The organization of environmental protection in Poland and the European Union is a mutual connection of competencies and a correlation of systems and rights according to national and EU laws. The legal system of the EU is the result of decades of cooperation undertaken by the will of the Member States known as the acquis communautaire. EU law has primacy over national law, which in practice means that in the event of a conflict between the provisions of national law and EU law, the national law is deemed inapplicable and needs to be adjusted by the Member State.